Exploring the associated characteristics of Internet gaming disorder from the perspective of various game genres - Liao, Zhenjiang; Chen, Xinxin; Huang, Shucai; Huang, Qiuping; Lin, Shuhong; Li, Yifan; Tang, Ying; Shen, Hongxian (Frontiers in Psychiatry, 2023)
Introduction: Although previous studies have reported several characteristics associated with Internet gaming disorder (IGD), the influence of game genre on IGD has rarely been investigated. This study thus aimed to compare demographic characteristics, gaming patterns, personality traits, and gaming motivations among players in different game genres, as well as identify the predictors of genre-specific IGD. Methods: Internet games were classified into four types: role-playing games (RPGs), strategy (STR) games, action shooter (ACS) games, and brain and skill (BRS) games. Chinese gamers (n = 5593) who usually played one of these games completed an anonymous online survey that included sociodemographic characteristics, gaming patterns, gaming motivations, the Chinese version of the Video Gaming Dependency Scale (VGD-S), and the Chinese Big Five Personality Inventory brief version. Results: Significant differences were found between the genre-specific groups regarding age, gender, relationship status, VGD-S score, gaming patterns, and personality traits (e.g., RPG and STR players were more vulnerable to developing IGD compared to ACS and BRS players). Multivariate logistic regression analyses showed that IGD predictors were slightly different within each genre-specific group after controlling for sociodemographic factors. Some predictors (e.g., daily gaming time and monthly gaming charge) were associated with IGD development within the genre-specific group. Conclusion: Individuals in each game genre exhibited distinct characteristics that might predict IGD development (e.g., gaming patterns and personality traits). Game genres should be considered in the early prevention and treatment of IGD to help high-risk individuals’ recovery. Additionally, more research should be conducted to explore RPG and STR game characteristics.